2020
DOI: 10.1093/scipol/scz060
|View full text |Cite
|
Sign up to set email alerts
|

The effect of collaboration with top-funded scholars on scientific production

Abstract: The theoretical model developed in this article predicts that collaboration with top-funded scientists positively affects the number of scientific publications of an individual scientist. Having combined data on funding and publication of Quebec scientists, this article empirically tests the theoretical predictions. This article examines numerous definitions of top-funded scientists as those in the top 10 per cent, or top 5 per cent in terms of total funding, funding from the public sector, and funding from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Further prominent examples include fostering commitment, trust, and a good relationship between collaborators (e.g., Chompalov and Shrum, 1999;Shrum et al, 2001Shrum et al, , 2007Bruneel et al, 2010) and the provision of funding, incentives, and rewards as well as motivating participants (e.g., Heller and Michelassi, 2012;Currie-Alder et al, 2018;Wagner et al, 2019). Furthermore, working with previous collaboration partners ( Chapman et al, 2018;Liang and Liu, 2018;Hewitt-Dundas et al, 2019), optimal team size and composition (e.g., Porac et al, 2004;Holl and Rama, 2019;Mirnezami et al, 2020), and working with partners with similar styles of working and objectives (e.g., Hara et al, 2003) are also regarded as effective, albeit less frequently. Some studies also highlight the definition of clear objectives (e.g., Bjerregaard, 2009;Begun et al, 2010;Lee and Mitchell, 2011), project planning and monitoring (e.g., Segalla, 1998;Barnes et al, 2002;Morandi, 2013), as well as an efficient and appropriate division of labor (e.g., Raadgever et al, 2012;Jeong and Choi, 2015;Haeussler and Sauermann, 2020).…”
Section: Insights Into Solutions To Collaboration Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further prominent examples include fostering commitment, trust, and a good relationship between collaborators (e.g., Chompalov and Shrum, 1999;Shrum et al, 2001Shrum et al, , 2007Bruneel et al, 2010) and the provision of funding, incentives, and rewards as well as motivating participants (e.g., Heller and Michelassi, 2012;Currie-Alder et al, 2018;Wagner et al, 2019). Furthermore, working with previous collaboration partners ( Chapman et al, 2018;Liang and Liu, 2018;Hewitt-Dundas et al, 2019), optimal team size and composition (e.g., Porac et al, 2004;Holl and Rama, 2019;Mirnezami et al, 2020), and working with partners with similar styles of working and objectives (e.g., Hara et al, 2003) are also regarded as effective, albeit less frequently. Some studies also highlight the definition of clear objectives (e.g., Bjerregaard, 2009;Begun et al, 2010;Lee and Mitchell, 2011), project planning and monitoring (e.g., Segalla, 1998;Barnes et al, 2002;Morandi, 2013), as well as an efficient and appropriate division of labor (e.g., Raadgever et al, 2012;Jeong and Choi, 2015;Haeussler and Sauermann, 2020).…”
Section: Insights Into Solutions To Collaboration Problemsmentioning
confidence: 99%
“…We selected the teams so as to ensure the coverage of a wide range of disciplines (including interdisciplinary teams) as well as different team sizes and constellations (including both Optimal team size and composition Empirical evidence (e.g., Mirnezami et al, 2020) Working with partners with similar styles of working and objectives Empirical evidence (e.g., Hara et al, 2003) academic-only and university-industry collaboration teams). The key criteria for sampling were the degree of (1) disciplinary and (2) organizational heterogeneity.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Amjad et al (2017) demonstrated that working with leading experts can lead to a successful career for young researchers. For the same reason, collaboration with top-funded scientists can be an opportunity for accumulating valuable experience and tacit knowledge, resulting in higher and better scientific production (Mirnezami, Beaudry, and Tahmooresnejad 2020). Wagner et al (2015) discovered a significant increase in the average number of collaborators per paper among Nobel Prize winners post-award compared to before the recognition.…”
Section: Literature Reviewmentioning
confidence: 99%